1971
DOI: 10.1111/j.1471-4159.1971.tb12034.x
|View full text |Cite
|
Sign up to set email alerts
|

STUDIES IN VIVO ON THE RELATIONSHIP BETWEEN BRAIN TRYPTOPHAN, BRAIN 5‐HT SYNTHESIS AND HYPERACTIVITY IN RATS TREATED WITH A MONOAMINE OXIDASE INHIBITOR AND L‐TRYPTOPHAN

Abstract: Abstract— The effect of l‐tryptophan loading upon the amount of 5‐HT accumulating in the brains of rats pretreated with a monoamine oxidase inhibitor was studied. The amount of brain 5‐HT accumulated increased with increasing tryptophan dosages and brain tryptophan concentrations up to a tryptophan dose of 120 mg/kg body wt. and a brain tryptophan of about 70 μg/g brain. Above this dose and concentration no further increase in brain 5‐HT accumulation occurred. After monoamine oxidase inhibition and tryptophan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
119
0
1

Year Published

1972
1972
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 648 publications
(126 citation statements)
references
References 20 publications
6
119
0
1
Order By: Relevance
“…These findings and recent experiments concerning the relation of cerebral 5-hydroxytryptamine to a syndrome of hyperactivity and hyperpyrexia (Grahame-Smith, 1971) would suggest that the model previously proposed for cerebral 5-hydroxytryptamine metabolism (Moir & Eccleston, 1968) should be modified. The diagram shown in Fig.…”
Section: Discussionmentioning
confidence: 93%
“…These findings and recent experiments concerning the relation of cerebral 5-hydroxytryptamine to a syndrome of hyperactivity and hyperpyrexia (Grahame-Smith, 1971) would suggest that the model previously proposed for cerebral 5-hydroxytryptamine metabolism (Moir & Eccleston, 1968) should be modified. The diagram shown in Fig.…”
Section: Discussionmentioning
confidence: 93%
“…Crow & Deakin (1977) suggested that the different behavioural components of the tranylcypromine/tryptophan syndrome might have different neurochemical bases. Conflicting experimental results might thus be explained by methods of quantification of the behaviour which emphasize different behavioural components, for example, automated recordings of activity (Grahame-Smith, 1971a) and ratings of headweaving and forepaw treading etc. (Jacobs, 1974).…”
Section: Introductionmentioning
confidence: 99%
“…The behaviour appears to be due to increased synthesis and 'spill-over' onto the postsynaptic receptors of brain 5-hydroxytryptamine (5-HT) (Grahame-Smith, 1971a); the behavioural changes have been used to investigate the way that various drugs alter 5-HT function in the central nervous system (see reviews of Green & Grahame-Smith, 1976a;Jacobs, 1976).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In animals the administration of a combination of L-tryptophan and a monoamine oxidase inhibitor leads to a characteristic behavioural syndrome (Hess Doepfner, 1961;Grahame-Smith, 1971), which in rats may be subdivided into various components including hyperactivity, hyper-reactivity, reciprocal forepaw treading, headweaving and hind limb abduction. A dopaminergic component of the syndrome has been proposed (Green & Grahame-Smith, 1974) on the basis of the inhibition of the syndrome by pretreatment of the animals with a-methyl-p-tyrosine, a drug which blocks the synthesis of dopamine.…”
Section: Discussionmentioning
confidence: 99%